miR-196a targeting LRIG3 promotes the proliferation and migration of cervical cancer cells - Qiu, Yunfen; Han, Qing; Lu, Hong; Shi, Chunming (Cellular and Molecular Biology, 2020)
In recent years, studies have found that miR-RNA plays a role in cell proliferation, differentiation, apoptosis and metabolism. Among them, miR-196a is closely related to cervical cancer. Therefore, this experiment investigates the effect of mir-196a expression on cervical cancer cells and related mechanisms. The expression level of miR-196a in the cervical cancer cell line was assayed with the RT-PCR method, and liposome transfection was used to investigate its up-regulation or down-regulation in cervical cancer cells. The CCK-8 method and flow cytometry were used to measure cervical cancer cell proliferation and apoptosis, while the Transwell assay was used to determine cell migration and invasion of each transfection group. Bioinformatics was used to predict the target gene of miR-196a, which was verified using dual luciferase report experiment and Western blot, and miR-196a was further transfected with si-LRIG3 to detect its reversal effect on miR-196a regulation. Inhibition of the expression of miR-196a significantly reduced the proliferation, migration and invasion of cervical cancer cells, and promoted their apoptosis. Results from dual luciferase assay showed that miR-196a and LRIG3 had direct targeting effects. Cell proliferation, migration and invasion were enhanced by a reduction in the expression level of LRIG3 protein after miR-196a inhibitor cells were transfected with si-LRIG3. The expression of miR-196a is up-regulated in cervical cancer, and it promotes the growth of cervical cancer by its targeting effect on LRIG3 expression, resulting in enhancement of the proliferation, migration and invasion ability of cervical cancer cells, and inhibition of apoptosis.